Implementación del sistema contable en el autoservicio "Mi Supermercado" del cantón Celica provincia de Loja; periodo 2023 - Bermeo Bermeo., Jasenia Paulina (2024)
In the current environment in which commercial businesses operate, accounting plays a fundamental role in decision making related to resource planning and optimization. This constitutes an essential tool in commercial enterprises when making decisions and drawing up a chart of accounts and manual to standardize and organize the recording of all financial transactions. The objective of the research is to design a customized accounting system that adapts to the needs of the self-service store “My supermarket” using a qualitative and quantitative approach through the application of scientific methods: deductive, inductive and mathematical. The accounting system of the self-service store was analyzed based on the collection of purchase and sales invoices, receipts, receipts of income and expenses, among other documents, during the period from June to August 2023. With the source documentation compiled and analyzed, we began with the chart of accounts and manual adapted to the company's needs. From there, we proceeded with the creation of the initial situation statement, the journal, the general ledger and the trial balance, and culminated with the preparation of the financial statements. Finally, based on the results obtained, it is concluded that the implementation of an Accounting System in the commercial establishment has provided clear data on its operations, reflected in the Financial Statements in accordance with Generally Accepted Accounting Principles and International Accounting Standards, allowing to determine that the self-service store is generating net profits and is operating profitably. Therefore, it is recommended that the Manager-Owner adopt the Accounting System designed, which is structured according to the needs of the self-service business, to facilitate the application of solutions that promote its economic and financial development.